2017
DOI: 10.1007/s10661-017-6236-4
|View full text |Cite
|
Sign up to set email alerts
|

Runoff of the herbicides triclopyr and glufosinate ammonium from oil palm plantation soil

Abstract: This study focused on the residue detection of the herbicides triclopyr and glufosinate ammonium in the runoff losses from the Tasik Chini oil palm plantation area and the Tasik Chini Lake under natural rainfall conditions in the Malaysian tropical environment. Triclopyr and glufosinate ammonium are post-emergence herbicides. Both herbicides were foliar-sprayed on 0.5 ha of oil palm plantation plots, which were individualized by an uneven slope of 10-15%. Samples were collected at 1, 3, 7, 15, 30, 45, 60, 90, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Meantime due to its strong water solubility (>500 g/L, at pH 5–9, 20°C) and stability (stable to light and hydrolysis at pH 5, 7, and 9), GLA could exist for a longer period and easily persist in the water environment 2,3 . Current research studies have found that residues of GLA have been detected in groundwater and surface water in countries such as China, Argentina, and Malaysia 4–6 . Although the concentrations are low, the residues are bound to increase as the use of GLA increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meantime due to its strong water solubility (>500 g/L, at pH 5–9, 20°C) and stability (stable to light and hydrolysis at pH 5, 7, and 9), GLA could exist for a longer period and easily persist in the water environment 2,3 . Current research studies have found that residues of GLA have been detected in groundwater and surface water in countries such as China, Argentina, and Malaysia 4–6 . Although the concentrations are low, the residues are bound to increase as the use of GLA increases.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Current research studies have found that residues of GLA have been detected in groundwater and surface water in countries such as China, Argentina, and Malaysia. [4][5][6] Although the concentrations are low, the residues are bound to increase as the use of GLA increases. More importantly, the hazard of GLA to non-target organisms has also been found, such as neurotoxicity and reproductive toxicity, especially in aquatic animals.…”
mentioning
confidence: 99%
“…Industrial oil palm cultivation is highly dependent on fossil fuel energy and external nutrient and chemical inputs. For instance, to control weeds in oil palm plantations, commercial growers rely heavily on the application of chemical herbicides (e.g., broad-spectrum glyphosate-based herbicides) which can pollute the environment and indiscriminately eliminate non-target or beneficial species (Shariff and Rahman, 2008;Choo et al, 2011;Singh et al, 2014;Tayeb et al, 2017;Dilipkumar et al, 2020;Pochron et al, 2020). Oil palm-livestock integration through targeted or prescribed grazing approach (i.e., the application of livestock grazing to attain specific vegetation management goals such as enhancing desirable plant communities and controlling invasive plant populations) can substitute herbicide use for weed management (Frost and Launchbaugh, 2003;Tohiran et al, 2017Tohiran et al, , 2019aBailey et al, 2019).…”
Section: Introductionmentioning
confidence: 99%